Intimacy and Exclusion : Religious Politics in Pre-Revolutionary Baden. - Herzog, Dagmar (Princeton studies in culture/power/history., 2014)
During the years leading up to the revolutions of 1848, liberal and conservative Germans engaged in a contest over the terms of the Enlightenment legacy and the meaning of Christianity--a contest that grew most intense in the Grand Duchy of Baden, where liberalism first became an influential political movement. Bringing insights drawn from Jewish and women's studies into German history, Dagmar Herzog demonstrates how centrally Christianity's problematic relationships to Judaism and to sexuality shaped liberal, conservative, and radical thought in the pre-revolutionary years. In particular,